Watch and learn the effectiveness of the MTRCB SPG TV rating system - Policarpio, Angela Micah Cantada 1992- (2013)
"This thesis looks into how the MTRCB SPG TV Rating System is followed and enforced by the families living in the National Capital Region. This is guided by the Theory of Planned Behavior and McQuail's structural approach to audience formation in its application of the ICT Literacy framework and Steps of Behavior Change. Both quantitative and qualitative research approaches are used in this study. Particularly, self administered survey, participant observations, family group discussions and focus interviews are employed. Results show that there are differences between parents' and children's perceptions. parents see their family communication as engaging and open to discussions while the children see the parents as authoritative and controlling. Children, however, are more knowledgeable of the SPG Rating System. The families also have different ways of implementing it. Watching SPG programs with the family as well as asking why a program is SPG-rated and their forms of enforcement; thereby, depicting coviewing and active TV mediation styles. However, even if the families know that there are scenes unsuited for children, watching such programs is difficult to avoid because they wanted to wait for that SPG-rated scene and to know why it is SPG-rated. The study further reveals that it is quite impossible for the parents' attention to be solely put on children's TV viewing."